Counselling Services: The Albatross of Students with Disabilities in the Pan African University in Ghana - Gyasi, Ficus; Hayford, Samuel K. (IJRDO- Journal of Educational Research, 2017)
Universities set up counselling centres to provide services for students, including those with disabilities, to mitigate the challenges they encounter while schooling, in order to enhance their participation in academic work and social life. However, investigation conducted by the researchers revealed that the Counselling Centre in Pan African University in Ghana has become an albatross to students with disabilities. This paper describes the factors that have turned the Counselling Centre into an albatross for students with disabilities in the Pan African University in Ghana. The purpose of the study was to ascertain whether or not counselling services in the Pan African University were accessible to students with disabilities. A sample of 18 students with disabilities (six visually impaired, six hearing impaired and six physically disabled, respectively) was purposefully selected using maximal variation approach. Semistructured interviews were used to collect data for the study. The researchers adopted thematic analysis to analyze the data. The results showed that students with disabilities were unable to access the much needed counselling service provided by the university due to barriers related to the location of the counselling centre and communication. These barriers adversely impacted on the students’ moral and academic achievements. The students suggested that the University should decentralize the counselling services to make the services more accessible. The researchers recommended that the University should provide in-service training focusing on issues in disabilities for the professional counsellors in the University.